The Minimalist and Maximalist Approaches in the TEFLIN: Towards the Empowerment of the General Indonesian Learners of English - Asim Gunarwan (TEFLIN, 2001)
Abstract: The point of departure of this paper is an assumption that the teaching of English in Indonesian public schools has not yielded the minimum expected result: English learners have not been empowered with the reading skill in English, let alone the other skills. Given that English has an elevated role to play in the new millennium, Indonesian learners should be empowered in this language for wider communicaÃÂtions. Two approaches are proposed, namely (1) the minimalist approach, in which reading ability is the sole objective of the teaching of English to students in general, the corrolary being the use of the translation method; and (2) the maximalist approach, in which